QUANTITATIVE ASSESSMENT OF AIRBORNE MICROBIAL LOAD IN CLINICAL AND ADJACENT ENVIRONMENTS - Vijay Krishanan; Kiran kumar, S; Karthick, K; Sindhuja, A; Mahalakshmi, J (The Bioscan, 2025)
Airborne microbial contamination in hospital environments poses a significant risk to infection control, especially in operating rooms. This study evaluates airborne microbial loads in six different hospital and adjacent locations through passive sampling using nutrient agar plates. Samples were exposed to air for 10 minutes and incubated for 48 hours to quantify colony-forming units (cfus). The highest microbial counts were observed near the bike stand outside the lab, while the immunology lab recorded the lowest counts. The findings underscore the importance of air quality monitoring and control strategies in healthcare settings.